Revisiting the initial reaction rates for TMS combustion and a new evidence for metastable silica nanoparticles in the gas-phase synthesis - Karakaya, Yasin; Somnitz, H.; Hermsen, A.; Gonchikzhapov, Munko; Kasper, Tina (Applications in Energy and Combustion Science)
Keywords: Metastable particles; Nanomaterials; Quartz-crystal-microbalance; Molecular-beam mass spectrometry; Tetramethylsilane; Reaction kinetics

Fiber-coupled plug-and-play heralded single photon source based on Ti:LiNbO3 and polymer technology - Kießler, Christian; Conradi, Hauke; Kleinert, Moritz; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (Optics Express)
A reliable, but cost-effective generation of single-photon states is key for practical quantum communication systems. For real-world deployment, waveguide sources offer optimum compatibility with fiber networks and can be embedded in hybrid integrated modules. Here, we present what we believe to be the first chip-size fully integrated fiber-coupled heralded single photon source (HSPS) module based on a hybrid integration of a nonlinear lithium niobate waveguide into a polymer board. Photon pairs at 810 nm (signal) and 1550 nm (idler) are generated via parametric down-conversion pumped at 532 nm in the LiNbO3 waveguide. The pairs are split in the polymer board and routed to separate output ports. The module has a size of (2 × 1) cm^2 and is fully fiber-coupled with one pump input fiber and two output fibers. We measure a heralded second-order correlation function of g_h(2)=0.05 with a heralding efficiency of η_h=3.5% at low pump powers
Keywords: Atomic and Molecular Physics; and Optics

Scholarship of Teaching and Learning (SoTL) als Motor für eine inter- und transdisziplinäre Hochschuldidaktik - Arnold, Maik; Vöing, Nerea; Reisas, Sabine (Hochschulbildung: Lehre und Forschung)
SoTL ist eine forschungsbasierte Haltung, die die Hochschullehre verbessern und innovieren will. Das deutschsprachige SoTL-Netzwerk hat fünf Thesen formuliert, die SoTL als Grundhaltung und Motor für Lehrentwicklung betonen. Der Beitrag diskutiert diese Thesen und stellt Aktivitäten des Netzwerks vor, die SoTL an Hochschulen und Universitäten fördern und vernetzen wollen. Dabei wird auch die Rolle der »Teacher-Researcher« hervorgehoben.

Identification and prediction of standard times in machining for precision steel tubes through the usage of data analytics - Weller, Julian; Roesmann, Daniel; Eggert, Sönke; von Enzberg, Sebastian; Gräßler, Iris; Dumitrescu, Roman (Procedia CIRP)

Zur Berechnug von flüssigkeitsseitigen Stoffübergagnskoeffizienten für Strukturpackungen - Mapura Ramirez, Luz Alejandra; Kenig, Eugeny Y.

Finite-data error bounds for Koopman-based prediction and control - Nüske, Feliks; Peitz, Sebastian; Philipp, Friedrich; Schaller, Manuel; Worthmann, Karl (Journal of Nonlinear Science)
The Koopman operator has become an essential tool for data-driven approximation of dynamical (control) systems in recent years, e.g., via extended dynamic mode decomposition. Despite its popularity, convergence results and, in particular, error bounds are still quite scarce. In this paper, we derive probabilistic bounds for the approximation error and the prediction error depending on the number of training data points; for both ordinary and stochastic differential equations. Moreover, we extend our analysis to nonlinear control-affine systems using either ergodic trajectories or i.i.d. samples. Here, we exploit the linearity of the Koopman generator to obtain a bilinear system and, thus, circumvent the curse of dimensionality since we do not autonomize the system by augmenting the state by the control inputs. To the best of our knowledge, this is the first finite-data error analysis in the stochastic and/or control setting. Finally, we demonstrate the effectiveness of the proposed approach by comparing it with state-of-the-art techniques showing its superiority whenever state and control are coupled.

Thermal and chemical structure of ethanol and 2-ethylhexanoic acid/ethanol SpraySyn flames - Gonchikzhapov, Munko; Kasper, Tina (Applications in Energy and Combustion Science)
Keywords: Nanoparticle synthesis; Flame spray pyrolysis; SpraySyn burner; Flame structure; Species distribution; Temperature distribution

Efficient time stepping for numerical integration using reinforcement learning - Dellnitz, Michael; Hüllermeier, Eyke; Lücke, Marvin; Ober-Blöbaum, Sina; Offen, Christian; Peitz, Sebastian; Pfannschmidt, Karlson (SIAM Journal on Scientific Computing)
Many problems in science and engineering require an efficient numerical approximation of integrals or solutions to differential equations. For systems with rapidly changing dynamics, an equidistant discretization is often inadvisable as it results in prohibitively large errors or computational effort. To this end, adaptive schemes, such as solvers based on Runge–Kutta pairs, have been developed which adapt the step size based on local error estimations at each step. While the classical schemes apply very generally and are highly efficient on regular systems, they can behave suboptimally when an inefficient step rejection mechanism is triggered by structurally complex systems such as chaotic systems. To overcome these issues, we propose a method to tailor numerical schemes to the problem class at hand. This is achieved by combining simple, classical quadrature rules or ODE solvers with data-driven time-stepping controllers. Compared with learning solution operators to ODEs directly, it generalizes better to unseen initial data as our approach employs classical numerical schemes as base methods. At the same time it can make use of identified structures of a problem class and, therefore, outperforms state-of-the-art adaptive schemes. Several examples demonstrate superior efficiency. Source code is available at https://github.com/lueckem/quadrature-ML.

Analysis and Modelling of the Deformation in the Manufacture of Flange-Contours by the Combined Friction-Spinning and Flow-Forming Process - Dahms, Frederik; Homberg, Werner (Lecture Notes in Mechanical Engineering)

Unboxing video effectiveness – Does speech matter? - Garnefeld, I.; Böhm, Eva; Hanf, L.; Helm, S. (2023 AMA Summer Academic Conference, San Francisco, CA)

The dark and bright side of online reviews in manufacturer online shops - Kessing, K.; Garnefeld, I.; Böhm, Eva (EMAC Annual Conference, Odense, Denmark)

Stimulating engagement with unboxing videos – Does speech matter? - Hanf, L.; Garnefeld, I.; Böhm, Eva; Helm, S. (EMAC Annual Conference, Odense, Denmark)

Low Power Streaming of Sensor Data Using Gray Code-Based Approximate Communication - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille; Wunderlich, Hans-Joachim (2023 53rd Annual IEEE/IFIP International Conference on Dependable Systems and Networks Workshops (DSN-W))

Overcoming the Miscibility Gap of GaN/InN in MBE Growth of Cubic InxGa1–xN - Zscherp, Mario Fabian; Jentsch, Silas Aurel; Müller, Marius Johannes; Lider, Vitalii; Becker, Celina; Chen, Limei; Littmann, Mario; Meier, Falco; Beyer, Andreas; Hofmann, Detlev Michael; As, Donat Josef; Klar, Peter Jens; et al. (ACS Applied Materials & Interfaces)
Keywords: General Materials Science

Home (Office) is where your Heart is - Marx, Julian; Stieglitz, Stefan; Brünker, Felix; Mirbabaie, Milad (Business & Information Systems Engineering)
Abstract Working conditions of knowledge workers have been subject to rapid change recently. Digital nomadism is no longer a phenomenon that relates only to entrepreneurs, freelancers, and gig workers. Corporate employees, too, have begun to uncouple their work from stationary (home) offices and 9-to-5 schedules. However, pursuing a permanent job in a corporate environment is still subject to fundamentally different values than postulated by the original notion of digital nomadism. Therefore, this paper explores the work identity of what is referred to as ‘corporate nomads’. By drawing on identity theory and the results of semi-structured interviews, the paper proposes a conceptualization of the corporate nomad archetype and presents nine salient identity issues of corporate nomads (e.g., holding multiple contradictory identities, the flexibility paradox, or collaboration constraints). By introducing the ‘corporate nomad’ archetype to the Information Systems literature, this article helps to rethink established conceptions of “home office” and socio-spatial configurations of knowledge work.
Keywords: Information Systems

Aware but not prepared: understanding situational awareness during the century flood in Germany in 2021 - Zander, K.K.; Nguyen, D.; Mirbabaie, Milad; Garnett, S.T. (International Journal of Disaster Risk Reduction)
Keywords: Geology; Safety Research; Geotechnical Engineering and Engineering Geology; Building and Construction

The potential of digital nudging to bridge the gap between environmental attitude and behavior in the usage of smart home applications - Stieglitz, Stefan; Mirbabaie, Milad; Deubel, Annika; Braun, Lea-Marie; Kissmer, Tobias (International Journal of Information Management)
Keywords: Library and Information Sciences; Computer Networks and Communications; Information Systems

Digital Nudge Stacking and Backfiring: Understanding Sustainable E-Commerce Purchase Decisions - Mirbabaie, Milad; Marx, Julian; Erle, Lukas (Pacific Asia Journal of the Association for Information Systems)

Analyse von Alterungsmechanismen im Hinblick auf die Effizienz von Haushaltskältegeräten - Paul, Andreas
Die Energieaufnahme von Haushaltskältegeräten ist seit den 1990er Jahren erheblich gesunken. Dieser Wert wird von den Herstellern im Neuzustand der Geräte unter Normbedingungen bestimmt. Wie jedes technische System unterliegen jedoch auch Haushaltskältegeräte einem Alterungsprozess, der zu einem Anstieg der Energieaufnahme über die Zeit führt. Im Rahmen dieser Dissertation wurde auf der Grundlage von 100 Messungen der Energieaufnahme, die an 32 Geräten über einen Zeitraum von 21 Jahren durchgeführt wurden, ein Alterungsmodell entwickelt. Dieses Modell ist das erste, das mit Hilfe von Daten der Energieaufnahme real gealterter Geräte entwickelt wurde. Es beschreibt einen Anstieg der Energieaufnahme von 27 % über die durchschnittliche Einsatzzeit eines Haushaltskältegeräts von 16 Jahren. Der stärkste Anstieg erfolgt in den ersten fünf Betriebsjahren. Durch Diffusionsvorgänge in dem im Gehäuse verbauten Polyurethan-Schaum wird das im Zellgas vorhandene Kohlenstoffdioxid durch Luft ersetzt. Hierdurch steigt die Wärmeleitfähigkeit des Schaums um ca. 33 % an, wodurch sich die Energieaufnahme der Geräte erhöht. Des Weiteren wurde der Einsatz von Paraffinen als Phasenwechselmaterial in Haushaltskältegeräten untersucht. Durch deren Einsatz konnte die Energieaufnahme gesenkt und die Funktionalität der Geräte gesteigert werden. Hierfür sind detaillierte Kenntnisse der Materialkenndaten der Paraffine notwendig. Die Wärmeleitfähigkeit der verschiedenen Paraffin-Stoffgruppen in der festen Phase ist jedoch bisher nur unzureichend untersucht worden. Daher wurde ein Messaufbau entwickelt, mit dem die Wärmeleitfähigkeit von festem Paraffin bestimmt werden kann, und es wurden entsprechende Messungen durchgeführt.

Second grader´s understanding of doubling and halfing in various representations - Schwerin, Imke; Häsel-Weide, Uta (International Symposium in Elementary Mathematics Teaching. Proceedings: New Directions in Elementary Mathematics Education)